Origin of photovoltaic losses in selenium solar cells with open-circuit voltages approaching 1 V. Issue 45 (7th November 2022) - Nielsen, Rasmus; Youngman, Tomas H.; Moustafa, Hadeel; Levcenco, Sergiu; Hempel, Hannes; Crovetto, Andrea; Olsen, Thomas; Hansen, Ole; Chorkendorff, Ib; Unold, Thomas; Vesborg, Peter C. K.
Abstract : The optoelectronic properties of the world's oldest photovoltaic material, selenium, are revisited using modern characterization techniques in state-of-the-art selenium solar cells with record open-circuit voltages. Abstract : Research on selenium solar cells is regaining momentum due to the exciting prospect of integrating a single-element, wide-bandgap (≈1.95 eV) photoabsorber in tandem with a lower bandgap photovoltaic device. Low temperature processing of selenium makes it a potentially inexpensive candidate for a top cell absorber that can easily be integrated with existing photovoltaic technology. However, single-junction selenium devices still exhibit a significant voltage deficit when compared to the Shockley–Queisser limit, despite recent efficiency improvements through device engineering. This calls for more detailed characterization of the selenium material properties linked to photovoltaic performance. In this work, we first fabricate large-area selenium solar cells with a record open-circuit voltage of 0.99 V and a pseudo fill factor of 80%. Then, we characterize the mobility-lifetime product, built-in voltage and low-temperature radiative recombination in these state-of-the-art devices. We attribute most of the V oc -deficit to non-radiative recombination in the selenium absorber. Thus, improving the bulk optoelectronic quality of selenium appears to be a more urgent need than the optimization of its device structure.